On the axiomatisability of the dual of compact ordered spaces - Abbadini, M; Reggio, L (Springer, 2020)
We provide a direct and elementary proof of the fact that the category of Nachbin’s compact ordered spaces is dually equivalent to an ℵ1-ary variety of algebras. Further, we show that ℵ1 is a sharp bound: compact ordered spaces are not dually equivalent to any SP-class of finitary algebras.